2017
DOI: 10.5114/cipp.2017.65847
|View full text |Cite
|
Sign up to set email alerts
|

Regulative theory of temperament versus affective temperaments measured by the temperament evaluation of Memphis, Pisa, Paris and San Diego Auto-questionnaire (TEMPS-A): a study in a non-clinical Polish sample

Abstract: backgroundThis study investigates the relationship between temperament traits postulated by Strelau's regulative theory of temperament (RTT) and Akiskal's affective temperaments. This study represents the first attempt to compare these two concepts in a non-clinical Polish sample. participants and procedureThe study involved 615 healthy Caucasian adults (395 women and 220 men) aged from 17 to 69 years (M = 30.79, SD = 9.69). Temperament traits postulated by the RTT were assessed with the Formal Characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…As Rihmer et al [22] have found, depressive, cyclothymic and anxious temperaments are more frequent in women, whereas hyperthymic and irritable temperaments predominate among men. Other authors have confirmed these results [17,19]. Experiences, skills and age have been indicated among the personal factors that contribute to information overload and its consequences, unlike sex or personality traits [1].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…As Rihmer et al [22] have found, depressive, cyclothymic and anxious temperaments are more frequent in women, whereas hyperthymic and irritable temperaments predominate among men. Other authors have confirmed these results [17,19]. Experiences, skills and age have been indicated among the personal factors that contribute to information overload and its consequences, unlike sex or personality traits [1].…”
Section: Introductionmentioning
confidence: 67%
“…Mazure and Maciejewski [39] suggested that women might rate higher on 2 cognitive styles defined as "concern about disapproval" and "need for control" than men, so they might be at a greater risk of affective disorders than men due to these cognitive styles, both in the absence and in the presence of stressful life events. In general, women experienced significantly greater emotional reactivity than men [40] and achieved higher scores on the affective temperaments scales, with the exception of hyperthymic (more "adaptive") temperament which was higher in men than women [17,19]. The identification of the negative emotions dominating in other than hyperthymic, i.e., depressive, cyclothymic, irritable and anxious affective temperaments, may help explain these results.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The females exhibited more depressive, cyclothymic and anxious temperaments than the males did, whereas the males exhibited more hyperthymic temperaments than the females did. No significant difference was found between the genders for irritable temperament (see also Blӧink et al, 2005;Borkowska et al, 2010;Oniszczenko, Stanisławiak, Dembińska-Krajewska, & Rybakowski, 2016;Vázquez, Tondo, Mazzarini, & Gonda, 2012).…”
Section: Table 2 Mean and Standard Deviation Comparisons For Affectivmentioning
confidence: 99%